DAMPAK PANDEMI COVID-19 TERHADAP HARGA SAHAM PT. INDOFARMA TBK - Hendrik Manossoh; Joanne Valesca Mangindaan (FEB Universitas Sam Ratulangi Manado, 2023)
The purpose of this study is to analyze the impact of COVID-19 pandemic on the share price of PT. Indofarma Tbk (INAF), as one state-owned enterprise in healthcare sector. This study analyses the impact of COVID-19 on share price in several pandemic event in Indonesia. This study specifically focuses on three COVID-19 pandemic events, namely the announcement of first confirmed COVID-19 case in Indonesia, the imposing of the first Large Scale Social Restriction (PSBB I), and the imposing of new normal policy. By comparing share price of INAF during the 30-day period before and after each pandemic event, the result of this study shows that there is a significant different of share price between before and after COVID-19 pandemic. This study documents the impact of COVID-19 on the share price of INAF.